2020
DOI: 10.1111/ner.13031
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Current Steering Technologies for Directional Deep Brain Stimulation Using a Computational Model That Incorporates Heterogeneous Tissue Properties

Abstract: Objective A computational model that accounts for heterogeneous tissue properties was used to compare multiple independent current control (MICC), multi‐stim set (MSS), and concurrent activation (co‐activation) current steering technologies utilized in deep brain stimulation (DBS) on volume of tissue activated (VTA) and power consumption. Methods A computational model was implemented in Sim4Life v4.0 with the multimodal image‐based detailed anatomical (MIDA) model, which accounts for heterogeneous tissue prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 33 publications
3
41
0
Order By: Relevance
“…However, as the current increases from 1 to 2 mA, VTAs enlarged and exceeded the GPi boundary from the ventral side (and sometimes medial side) into undesired side effect regions such as the optic tract or the internal capsule (Figure 3C, blue). Consistent with previous findings, the VTAs with the single-segment monopole (configuration 1) generated the most axially asymmetric and largest VTA at the cathodic contact (Zhang et al, 2019). For the vertically stacked two-segment monopole configuration (configuration 2b), at 1 mA current amplitude, the VTA elongated dorsally along the lead and activates more structures dorsal to the GPi such as the medial medullary lamina FIGURE 3 | VTAs for various configurations: (A) 1.5 mm vertical spacing with 1 mA current, settings 1, 2a, and 3 (see methods), (B) 1.5 mm vertical pacing with 1 mA current, settings 2b, 4, and 5, (C) 1.5 mm vertical spacing with 2 mA current, settings 1, 2a, and 3, (D) 1.5 mm vertical pacing with 2 mA current, settings 2b, 4, and 5, (E) 0.5 mm vertical spacing with 1 mA current, settings 2b, 4, and 5, (F) 0.5 mm vertical spacing with 2 mA current, settings 2b, 4, and 5, marron = VTA inside of GPi, orange = VTA between GPe and GPi (medial medullary lamina), yellow = VTA inside of GPe, blue = VTA outside of GP.…”
Section: Vta Volumesupporting
confidence: 91%
See 2 more Smart Citations
“…However, as the current increases from 1 to 2 mA, VTAs enlarged and exceeded the GPi boundary from the ventral side (and sometimes medial side) into undesired side effect regions such as the optic tract or the internal capsule (Figure 3C, blue). Consistent with previous findings, the VTAs with the single-segment monopole (configuration 1) generated the most axially asymmetric and largest VTA at the cathodic contact (Zhang et al, 2019). For the vertically stacked two-segment monopole configuration (configuration 2b), at 1 mA current amplitude, the VTA elongated dorsally along the lead and activates more structures dorsal to the GPi such as the medial medullary lamina FIGURE 3 | VTAs for various configurations: (A) 1.5 mm vertical spacing with 1 mA current, settings 1, 2a, and 3 (see methods), (B) 1.5 mm vertical pacing with 1 mA current, settings 2b, 4, and 5, (C) 1.5 mm vertical spacing with 2 mA current, settings 1, 2a, and 3, (D) 1.5 mm vertical pacing with 2 mA current, settings 2b, 4, and 5, (E) 0.5 mm vertical spacing with 1 mA current, settings 2b, 4, and 5, (F) 0.5 mm vertical spacing with 2 mA current, settings 2b, 4, and 5, marron = VTA inside of GPi, orange = VTA between GPe and GPi (medial medullary lamina), yellow = VTA inside of GPe, blue = VTA outside of GP.…”
Section: Vta Volumesupporting
confidence: 91%
“…Recent modeling studies have now extended the VTA calculation to segmented DBS leads. Activation of a single electrode segment of these leads resulted in a shift in laterality of the VTA, sometimes known as directional DBS (Buhlmann et al, 2011 ; Zhang et al, 2019 ). However, there have been very few studies where bipolar settings have been used to model the VTA (Buhlmann et al, 2011 ; Duffley et al, 2019 ), and among those that have, homogeneous tissue models were used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coactivation allows for multiple contacts to be stimulated as if they were a single electrode (see below). In a modeling study, coactivation was shown to be associated with lower power consumption than MICC due to lowered impedance at the electrode-tissue interface [ 32 ].…”
Section: Update On Stimulationmentioning
confidence: 99%
“…The use of simple programming protocols, such as the activation of a single directional segment, has proved to be effective in the vast majority of cases [13]. Directional multiple-electrode programming configurations, whether using independent current controllers or interleaving, may provide additional nuances in programming strategies, but may also result in increased programming complexity [59], changes to battery power consumption, and reduction in the laterality of the volume of activation [60]. To assist with DBS programming, DBS producers developed innovative software platforms for functional mapping, as well as tools for visualization of the volume of neural activation.…”
Section: Discussionmentioning
confidence: 99%